Immune privilege in hair growth - Westgate, G E; Craggs, R I; Gibson, W T (Journal of investigative dermatology, 1991)
Immunostaining techniques were used to investigate the relationship between immune cells, proteoglycan, and class I MHC distribution in skin during the hair cycle in rats. The growth stage, anagen, was characterized by absence of class I MHC staining on most cells of the lower follicle and presence of chondroitin proteoglycan in the follicle sheath and dermal papilla. Immune cells were few in number and not associated with follicles. Dramatic changes were observed during regression in catagen; class I MHC was expressed on all follicle epithelium, large numbers of activated macrophages aggregated around the follicles, and the chondroitin proteoglycans disappeared from the follicle sheath and dermal papilla. During the resting stage, telogen, class I MHC remained on cells of the secondary germ, but macrophages and chondroitin proteoglycans were absent. These observations lead us to propose a hypothesis of immune privilege in hair growth.